ANALYSIS OF TRAFFIC ACCIDENTS USING GEOGRAPHIC INFORMATION SYSTEMS (GIS): A CASE STUDY OF THE CITY OF CONSTANTINE, ALGERIA - Benchenna Abdelali; Moufida Bouguebrine; Meddour Oualid; Redjal Omar (International Journal of Innovative Technologies in Social Science, 2024)
Algeria has experienced both information and technological important revolution, in addition to the growing population in cities, and especially Constantine, the need to make appropriate decisions for solving many problems is necessary, including traffic accidents, which are one of the most worrying subjects causing anxiety to the inhabitants of Constantine and the Algerian society, these accidents have increased dramatically, causing the exhaustion of human and material resources. It has therefore become necessary to contain it by using systems that help support modern decisions, including Geographic Information Systems GIS, which are considered a tool with great potential in spatial analysis. In this article we will try to focus on the importance of spatial and statistical analysis of traffic accidents in Constantine, it is mainly to estimate their percentage, as we found through analysis models such as the neighborhood link and direction of propagation.....etc. a strong concentration of traffic accidents is located in the commune of Constantine, which has strong economic activities, and from there we find that there is a strong link between the movement of the population and traffic accidents.